Whither Keynesian probability? Impolite techniques for decision-making. Issue 5 (2nd September 2016) - Zappia, Carlo
Abstract: The critical literature on Keynes has provided extensive analysis of why individual agents may find convenient to adopt a " conventional judgement", and what he meant by "polite techniques" used to save their faces as "rational, economic men." This paper concentrates instead on impolite techniques of thought suited to deal with Keynesian uncertainty. The paper suggests that the thread going from Keynes's Treatise on Probability to the General Theory and its defence provides a positive analysis of decision-making under uncertainty, and that placing emphasis on this positive analysis simply means adhering to Keynes's long-standing commitment to a (surely peculiar) probabilistic set-up.